SISTEM PREFEKTORAL DALAM PENATAAN ORGANISASI PERANGKAT DAERAH DI JAWA TENGAH (STUDI KASUS KOTA SEMARANG) - Gustine, Queenia Brainabila; Harsasto, Priyatno; ., Fitriyah (Journal of Politic and Government Studies, 2018)
Abstract, Restructuring of the regional government organization are based on the instructions of Government Regulation Number 18 of 2016 that makes local government are taking a steps to downsizing their organization either by removing some of the organizations or combine several functions in order to actualize the Principle of Right Sizing. However, in law number 23 of 2014, downsizing system is not mandatory, so the government of Semarang City does not downsizing their structure and not focusing on efficiency. The problems that raised in this research is: How was the process of restructuring the regional government organization in Semarang City? How the relationship formed between the Government of Cental Java and Government of Semarang City? The purpose of this study is to explain the process of restructuring the regional government organization in Semarang City and explain the relationship formed between the Government of Cental Java and Government of Semarang City.The research was conducted using autonomy theory. The method used in this research is qualitative method. Data collection techniques were conducted using interviews with resource persons, written document review, and supporting literature.The result of research, restructuring regional government organization in Semarang City focused on the principle of right sizing, not in efficiency, so that Semarangâ€™s city regional government unit is fixed and classified as a large organization , i.e. 52 unit. In law Number 23 of 2014 there is a clear division of authority between levels of government, so that the realtionship between the Government of Cental Java and Government of Semarang City become hierarchical. But this relation can not yet become efficient because the institiution as the coordinator, namely â€œCabang Dinasâ€ has not been formed.Key words: Intitutional reform, Restructuing regional government organization.